Odpowiedzi

2010-03-28T18:07:22+02:00
A)(3-2x)-(X+4)-(2x+5)=(3X-4)-(5X+7)
3-2x-x-4-2x-5=3x-4-5x-7
-6-5x=-2x-11
-3x=-5/(-3)
x=5/3

b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(X+7)
4-x-2x-3+x-4=-2x+3-x-7
-3-2x=-3x-4
x=-1

C)4x-5+x-7-2x-8=-3x+4-x-6
3x-20=-4x-2
7x=18/7
x=18/7

d)-(4-2X)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
-8=8x-13
8x=5/8
x=5/8

:)

2010-03-28T18:13:41+02:00
A)(3-2x)-(X+4)-(2x+5)=(3X-4)-(5X+7)
3-2x-x-4-2x-5=3x-4-5x-7
-2x-x-2x-3x+5x=-3+4+5-4-7
-3x=-5|:(-3)
x=5/3

b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(X+7)
4-x-2x-3+x-4=-2x+3-x-7
-x-2x+x+2x+x=-4+4+3-7
x=-4

c)4x-5+x-7-2x-8=-3x+4-x-6
4x+x-2x+3x+x=5+7+8+4-6
7x=18|:7
x=18/7= 2 i 4/7

d)-(4-2X)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
2x-2x-3x-2x-3x=4+4-1-5-7
-8x=-5|:(-8)
x=5/8
2010-03-28T18:14:12+02:00
A)(3-2x)-(X+4)-(2x+5)=(3X-4)-(5X+7)
3-2x-x-4-2x-5=3x-4-5x-4-7
-2x-x-2x-3x+5x=-4-4-7-3+4+5
-3x=-9 /÷(-3)
x=3
b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(X+7)
4-x-2x-3+x-4=-2x+3-x-7
-x-2x+x+2x+x=3-7-4+3+4
x=-1
C)4x-5+x-7-2x-8=-3x+4-x-6
4x+x-2x+3x+x=4-6+5+7+8
7x=18 /÷7
x=18/7
x=2 4/7
d)-(4-2X)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4x+2x-2x-4=3x-1+2x-5-7+3x
-4x+2x-2x-3x-2x-3x=-1-5-7+4
-12x=-9 /÷(-12)
x=0,75